Bank risk-taking and monetary policy transmission: Evidence from China - Xiaoming Li; Zheng Liu; Yuchao Peng; Zhiwei Xu (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
We study the impact of China's 2013 implementation of Basel III on bank risk-taking and its responses to monetary policy shocks using confidential loan-level data from a large Chinese bank. Guided by theory, we use a difference-in-difference identification, exploiting cross-sectional differences in lending behaviors between highrisk and low-risk bank branches before and after the new regulations. We find that, through a risk-weighting channel, changes in regulations significantly reduced bank risktaking, both on average and conditional on monetary policy easing. However, banks reduce risk-taking by increasing lending to ostensibly low-risk state-owned enterprises (SOEs) under government guarantees, despite their low average productivity.
URN:NBN:fi:bof-202110292073
Keywords: E52; G21; G28; 330; bank risk-taking; banking regulations; risk-weighting; monetary policy; difference-in-difference; China